Development Learning Management System Utilizing Google Workspace Integrated with Wordwall Based on Gamification in Non-Formal Education - Elvirawaty; Alwen Bentri; Abna Hidayati; Ulfia Rahmi (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to develop and validate a Google Workspace-based Learning Management System (LMS) integrated with gamification-based Wordwall for science learning in non-formal education at the junior high school level. The method used is R&D research with the ADDIE model, limited to the implementation stage. At the analysis stage, it was found that students need flexible, interactive, and enjoyable learning media. The design stage produced a learning flow and an intuitive LMS interface. The development stage resulted in an LMS validated by three experts with very valid results (media 87.0%, material 90.0%, language 92.0%). The implementation stage was conducted through practical tests by teachers and students, with average scores of 95.48% and 91.67%, categorized as very practical. In conclusion, the developed LMS is declared valid and practical, and has the potential to become an innovative, interactive, and relevant science learning solution in the context of non-formal education.